Formal Assessment of Teamwork Among Cancer Health Care Professionals in Three Large Tertiary Centers in Nigeria (2020)
PURPOSE There are strategies to bring quality cancer care to underserved patients, but poor use of the principles of teamwork is a major barrier to achieving quality services. The intent of this study was to assess teamwork as perceived by health care workers caring for patients with cancer. METHODS We conducted a survey among health care professionals in cancer care at 3 tertiary centers in southwestern Nigeria from July to November 2016. Respondents rated teamwork using the Safety Attitudes Questionnaire; we focused on the teamwork climate subscale comparing health care providers and institutions using analysis of variance and on collaboration using logistic regression. RESULTS Three hundred seventy-three professionals completed the survey: 177 physicians (47%), 51 nurses (14%), 21 pharmacists (6%), 31 laboratory technicians (8%), and 88 others (24%); 5 (1%) participants had missing professional information. The average teamwork climate score across all professionals in the study was 70.5 (SD = 24.2). Pharmacists rated the teamwork climate the lowest, with a mean score of 63.9 (SD = 29.5); nurses and laboratory technicians rated teamwork higher, with means of 74.5 (SD = 21.7) and 74.2 (SD = 27.1), respectively; and physicians rated teamwork 66.0 (SD = 23.6). Collaboration with other health care providers was reported as poorer by physicians compared with nurses and pharmacists. CONCLUSION Although overall teamwork scores were consistent with ambulatory studies in the United States, important subgroup variations provide targets for intervention. Physicians rated collaboration as poor both intraand interprofessionally. Pharmacists rated interprofessional teamwork with nurses as poor. Efforts to transform cancer care must focus on building trust among the key stakeholders. This is critical in low-resource settings, which must maximize the use of limited resources to improve patient outcomes.